HOMOFOBİNİN ANAYASAL ÜRETİMİ: ANAYASA MAHKEMESİ VE EŞCİNSELLİK - (:unkn) unknown (My University, 2018)
Bu makalede Anayasa Mahkemesinin eşcinsellik konusundaki ka-rarlarının üzerinde durulmuştur. Altı temel karara odaklanılan bu çalış-mada ulaşılan temel sonuç, Mahkeme’nin heteronormativist bir yaklaşımiçinde olduğu, bu yaklaşımı uyarınca da içermeci bir ayrımcılık ürettiği-dir. Mahkeme’nin kararlarındaki dildeki özensizliğin ise homofobik ön-yargılarla yüklü olduğu izlenimine ulaşılmıştır.

This article focuses on the decisions of the Turkish Constitutional Court about homosexuality. The article focuses on six key decisions and reaches the conclusion that the Court has a heteronormative approach which induces an internal discrimination. It was also concluded that the language used by the Court contains homophobic prejudices.
CONSTITUTIONAL PRODUCTION OF HOMOHOBIA: THE TURKISH CONSTITUTIONAL COURT AND HOMOSEXUALITY
Keywords: Hukuk